THEORITICAL ESTIMATION OF STRENGTH OF OVER LAP JOINING OF SHEETS - Ahmed M. Almukhtar (Journal of Engineering, 2005)
One of the main purposes of this study is to understande the reason of determining the standared of the parameters for overlap spot welding test, which is based on the thickness and overlap distances. The overlap joint is the most convential joining for the spot and riveting joint. The analysis of riveted and welded connection involves so many indeterminate factors that an exact solution is impossible. Nevertheless, by making certain simplifying assumption The most significant of these assumptions is that when the applied load passes through the centroid of the spotted region and the rotation angle will be small. By using the classical fracture theory, Misses and bending beam theory. The result which explain the behavior of the junction to the applied load, and to the rotational angle which depend on theield strength of the base metal and on the maximum load of the welded joint. The ditlerent paramcters were affected on the rotation of the welded joint and fracture load. Here, Tailure of the test sample is defined as the *fracture initiation", which corresponds to the peak load as discussed earlierTwo theories were applied with simple assumptions which used to reach the final formula in which suitable for lap welded joint. Also the mechanism of fracture and initation of crack have been examined.